That's why we click a study on the determinants of formation among selected adolescent cliques in UP Diliman - Caraan, Melissa Nadine C. (College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT Clique is one of the most common and influential friendship structure during adolescence. Its formation must then be explored in order to form meaningful and worthwhile relationship during adolescence. In this study, twenty homogenous cliques (113 adolescents) were purposively asked to participate in a focus group discussion to explore the determinants in clique formation and to identify differences in gender and its effect on the determinants of the clique formation. Results showed that the initial determinants of adolescent clique formation were proximity and similarity, the former being the most frequently identified important determinant. Gender differences in male and female cliques were not found on the identified determinant but on the quality of their relationship: male cliques consider physical proximity while female cliques consider functional proximity as a determinant. The activities done by the cliques also differ: male cliques? activities are mostly leisure and recreational while female engage in more intimate activities like chatting. This study established the importance of friendship, most specifically cliques during the adolescent years as it promotes friendship and a sense of belongingness among adolescents. This study has a lot of implications, but the most significant one that can be applied to the University is the continuance of the University?s Freshman Block System (SSC-08-87) to help them adjust well and form friendship and camaraderie among themselves.